2010
DOI: 10.1002/jmri.22153
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of in vivo determination of forearm muscle volume using 3.0 T magnetic resonance imaging

Abstract: Purpose: To apply magnetic resonance imaging (MRI) as a tool for quantifying muscle volume of forearm muscles feasibility and reliability of volume estimation of the flexor carpi ulnaris (FCU) and the extensor carpi ulnaris (ECU). Materials and Methods:Forearms of 10 subjects were scanned twice. Muscle volumes were calculated from manual outlines on axial slices, slice thickness, and the number of slices. Observer agreement and repeatability were estimated using intraclass correlation, coefficient of variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 11 publications
1
25
0
2
Order By: Relevance
“…While previous studies examining the reproducibility of skeletal muscle MR imaging measures across multiple centers have been limited, reproducibility within centers has been reported. For example, MR imaging measures of the size of forearm muscles were reported to have CVs of 0.8%-5.7% (15). Also, Deoni et al (16) reported a CV of 8% both within and across centers in repeated T2 measures of the brain.…”
Section: Musculoskeletal Imaging: Multicenter Study Of Mr Imaging Andmentioning
confidence: 99%
“…While previous studies examining the reproducibility of skeletal muscle MR imaging measures across multiple centers have been limited, reproducibility within centers has been reported. For example, MR imaging measures of the size of forearm muscles were reported to have CVs of 0.8%-5.7% (15). Also, Deoni et al (16) reported a CV of 8% both within and across centers in repeated T2 measures of the brain.…”
Section: Musculoskeletal Imaging: Multicenter Study Of Mr Imaging Andmentioning
confidence: 99%
“…; Smeulders et al. ), but fascicle orientations and pennation angles cannot be inferred from these scans.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies exploited conventional anatomical magnetic resonance imaging (MRI) to derive muscle architecture (Albracht et al 2008;B€ ol et al 2011). Anatomical T 1 -and T 2 -weighted scans provide sufficient contrast for quantification of muscle volume (Albracht et al 2008;Smeulders et al 2010), but fascicle orientations and pennation angles cannot be inferred from these scans.…”
Section: Introductionmentioning
confidence: 99%
“…Les exemples suivants illustrent la capacité de la RMN à identifier de subtils changements de trophicité du muscle. Suite à une injection de toxine botulique dans le gastrocnémien d'enfants infirmes moteurs cérébraux, une diminution de la masse de ce muscle de 4 % fut mesurée, compensée par une augmentation de 4 % de la masse du soléaire (Williams et al 2013 considéré (Smeulders et al 2010). Les effets d'un « désentraînement » faisant suite à des semaines de protocoles d'exercices concentriques et excentriques combinés à des restrictions de perfusion ont été évalués et ont montré une dépendance de la perte de trophicité au protocole d'entraînement (Yasuda et al 2015).…”
Section: La Trophicité Du Muscle Squelettiqueunclassified